Analysis of the association between high workload and musculoskeletal pain in public school teachers according to physical activity level - Furuta, Debora T. [UNESP]; Tebar, William R.; Beretta, Victor S. [UNESP]; Tebar, Fernanda Gil [UNESP]; de Carvalho, Augusto C. [UNESP]; Leoci, Isabella C. [UNESP]; Delfino, Leandro D. [UNESP]; Ferrari, Gerson; Silva, Claudiele C.M. [UNESP]; Christofaro, Diego G.D. [UNESP] (SAGE Publications, 2024)
BACKGROUND: A high workload has been associated with musculoskeletal pain in public school teachers. However, the hypothesis of the present study was that physical activity (PA) practice is able to attenuate this association. OBJECTIVE: To analyze the associations between high workload with musculoskeletal pain according to PA levels in public school teachers. METHODS: Teachers (n = 239) from 13 public schools were evaluated. Workload was assessed using a Likert scale in which teachers reported their perception of their work routine as: very low, low, regular, high, and very high. Musculoskeletal pain and PA were assessed using questionnaires. Multivariate logistic regression models were used to investigate the association of high workload with PA levels and musculoskeletal pain in different body regions, compared to participants with normal workload, adjusted by sex, age, and socioeconomic status. RESULTS: A high workload was associated with higher chances of reporting pain in the wrists and hands (OR = 3.55; 95% CI = 1.27-9.89), knee (OR = 3.09; 95CI%  = 1.09-8.82), and feet and ankles (OR = 3.16; 95% CI = 1.03-9.76) in less active teachers. However, these associations were not observed in teachers considered more active. CONCLUSION: PA practice is able to act as a good protector against musculoskeletal pain in teachers, even in individuals with a high workload.